High-Q Resonances Enabled by Bound States in the Continuum for a Dual-Parameter Optical Sensing - Hongshun Liu; Yuntao Pan; Hongjian Lu; Zongyu Chen; Xuguang Huang; Changyuan Yu (Photonics)
Optical sensing technologies, particularly refractive index and temperature sensing, are pivotal in biomedical, environmental, and industrial applications. This study introduces a dual-parameter all-dielectric transmissive grating sensor leveraging symmetry-protected bound states in the continuum (BICs). A one-dimensional silicon grating on a silica substrate was designed and analyzed using finite element analysis software. The proposed grating structure enables the excitation of two distinct BICs, both exhibiting high quality factors (Q-factors) of <semantics>QI=8.03×104</semantics> for Mode I and <semantics>QII=4.48×104</semantics> for Mode II. These modes demonstrate significantly different sensing characteristics due to their unique field distributions: Mode I predominantly confines its electromagnetic field within the grating slits, achieving an outstanding refractive index (RI) sensitivity of <semantics>SRII=406 nm/RIU</semantics> with a minor thermal sensitivity of <semantics>STI=0.052 nm/°C</semantics>. In contrast, Mode II concentrates its field energy in the silicon substrate, resulting in enhanced thermal sensitivity of <semantics>STII=0.078 nm/°C</semantics> while maintaining a refractive index sensitivity of <semantics>SRIII=220 nm/RIU</semantics>. This complementary sensitivity profile between the two modes establishes an ideal platform for developing a dual-parameter sensing system capable of simultaneously monitoring both refractive index variations and temperature changes. These results highlight the correlation between mode field distribution characteristics and sensing sensitivity performance, and enabling high Q-factor dual-parameter sensing with potential applications in lab-on-a-chip systems and real-time biomolecular monitoring.